2017
DOI: 10.1186/s13048-017-0316-5
|View full text |Cite
|
Sign up to set email alerts
|

Identification of factors that impact recurrence in patients with borderline ovarian tumors

Abstract: BackgroundThe lack of consensus around best practices for management of borderline ovarian tumors (BOT) is, in part, to the lack of available data and of clarity in interpreting relationships among various factors that impact outcomes. The objective of this study was to identify clinicopathological factors that impact prognosis of patients with borderline ovarian tumors (BOT) and to address features of this disease with the objective of providing clarity in decision making around management of BOT.ResultsA tot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
18
2
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 42 publications
3
18
2
2
Order By: Relevance
“…The safety of ipsilateral ovarian reservation for BOTs has been seldom evaluated in the literature. Ovarian cystectomy to spare the ipsilateral ovary/ovaries improved the risk of recurrence [ 2 , 15 , 31 , 32 ], consistent with our findings. However, this procedure had no significant impact on OS in patients with BOTs.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The safety of ipsilateral ovarian reservation for BOTs has been seldom evaluated in the literature. Ovarian cystectomy to spare the ipsilateral ovary/ovaries improved the risk of recurrence [ 2 , 15 , 31 , 32 ], consistent with our findings. However, this procedure had no significant impact on OS in patients with BOTs.…”
Section: Discussionsupporting
confidence: 89%
“…For BOTs, consensus has also not been reached on the indications and roles of adjuvant chemotherapy. This treatment method has not been identified in this study or in previous studies as a significant favorable factor for the prognosis of patients with BOTs [ 15 , 26 ]. Trope et al [ 37 ] demonstrated that adjuvant therapy showed no prognostic benefit but had serious toxicity.…”
Section: Discussionmentioning
confidence: 77%
“…Those with an elevated baseline of CA-125 had a 87% PFS at 3 years and those with a normal baseline of CA-125 had a 97% PFS at 3 years. 20,22,23 Another important prognostic factor for serous BOTs is the presence of micropapillary patterns, which has a 3 year PFS rate of 76%, compared to the absence of micropapillary patterns, which has a 3 year PFS of 94%. 20,[24][25][26]…”
Section: Discussionmentioning
confidence: 99%
“…Stage T1 defined in AJCC 3rd is the same as stage I in FIGO 2014, except that stage Ic in FIGO 2014 is further divided into Ic1, Ic2 and Ic3 stages. The inclusion and exclusion criteria for these patients has been described previously [ 15 ].…”
Section: Methodsmentioning
confidence: 99%
“…Current consensus states that fertility preserving surgery is associated with an increased risk of recurrence [ 8 12 ]. Data from ours and other groups showed that certain styles of fertility preserving surgery may have a higher risk of recurrence than the others [ 13 15 ]. However, fertility preserving surgery was not shown to compromise overall survival in these patients [ 16 19 ].…”
Section: Introductionmentioning
confidence: 93%